In Real Life, Low-Level HER2 Expression May Be Associated With Better Outcome in HER2-Negative Breast Cancer: A Study of the National Cancer Center, China - Li, Yiqun; Abudureheiyimu, Nilupai; Mo, Hongnan; Guan, Xiuwen; Lin, Shaoyan; Wang, Zijing; Chen, Yimeng; Chen, Shanshan; Li, Qiao; Cai, Ruigang; Wang, Jiayu; Luo, Yang; et al. (Frontiers in Oncology, 2022)
Background: To characterize the clinical, pathological features and survival of patients with HER2-low breast cancer in China. Methods: The China National Cancer Center database was used to identify 1433 metastatic breast cancer patients with HER2-negative disease diagnosed between 2005 and 2015. Clinicopathological features, survival and prognosis information were extracted. Overall survival (OS) was estimated using the Kaplan–Meier method and compared using the log-rank test. Prognostic factors associated with OS were analyzed using Cox regression model with 95% confidence interval (95%C.I.). Results: The number of HER2-low and HER2-zero tumors were 618 (43.1%) and 815 (56.9%) out of 1433 tumors, respectively. The proportion of hormone receptor (HR) positive tumors was significantly higher in HER2-low tumors than in those with HER2-zero tumors (77.8% vs 69.2%, p <0.001). Patients with HER2-low tumors survived significantly longer than those with HER2-zero tumors in the overall population (48.5 months vs 43.0 months, p =0.004) and HR-positive subgroup (54.9 months vs 48.1 months, p =0.011), but not in the HR-negative subgroup (29.5 months vs 29.9 months, p =0.718). Multivariate regression analysis revealed that HER2-low tumors were independently associated with increased OS in HER2-negative population (HR: 0.85, 95% CI: 0.73-0.98, p =0.026). Conclusion: Our findings demonstrate that HER2-low tumors could be identified as a more distinct clinical entity from HER2-zero tumors, especially for the HR-positive subgroup. A more complex molecular landscape of HER2-low breast cancer might exist, and more precise diagnostic algorithms for HER2 testing could be investigated, thus offering new therapeutic targets for breast cancer treatment.